2019
DOI: 10.14221/ajte.2018v44n2.3
|View full text |Cite
|
Sign up to set email alerts
|

Health and Physical Education Teacher Education 2.0: Pre-service Teachers’ Perceptions on Developing Digital Twitter Skills

Abstract: The advent of Web 2.0 technologies such as Twitter are reflective of an improved capacity for global educative collaboration. Yet there is an absence of research determining the potential of social media within Health and Physical Education Teacher Education (H-PETE). The aim of this paper was to therefore determine pre-service teachers' (PSTs) perceptions of the potential of using Twitter within H-PETE training. The study was underpinned by a constructivist online learning framework. PSTs (n=35) enrolled at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
(51 reference statements)
1
19
0
Order By: Relevance
“…In relation to ITE degrees, social media use highlights how connections made can assist PSTs to transform their connections to the profession (Bull et al, 2008;Carpenter, 2015;Carpenter & Morrison, 2018;Harvey & Hyndman, 2018;Hyndman & Harvey, 2019;Kelly & Antonio, 2016;Lemon, 2016;Paris, Boston & Morris, 2015;Nielsen, Moll, Farrell, McDaid & Hoban, 2013;Wright, 2010). Connection and networking offered by social media in ITE contexts can support PSTs development of linking to their peers (Carpenter, 2015;Carpenter & Morrison, 2018;Duncan-Howell, 2008;Lemon, 2016;Hyndman & Harvey, 2019) while honing reflective practice that illuminates the individual value of skill development associated to the act of being a teacher (Wright, 2010). Use also supports the shift of feeling isolated while in educational settings during the professional experience component of PSTs studies with opportunity for access to conversation with peers, lecturers and the profession and global resources to support their confidence to articulate professional growth (Bull et al, 2008;Carpenter, 2015;Carpenter & Morrison, 2018;Lemon, 2016;Lemon, Molloy & Hocking, 2015).…”
Section: Social Media In Initial Teacher Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…In relation to ITE degrees, social media use highlights how connections made can assist PSTs to transform their connections to the profession (Bull et al, 2008;Carpenter, 2015;Carpenter & Morrison, 2018;Harvey & Hyndman, 2018;Hyndman & Harvey, 2019;Kelly & Antonio, 2016;Lemon, 2016;Paris, Boston & Morris, 2015;Nielsen, Moll, Farrell, McDaid & Hoban, 2013;Wright, 2010). Connection and networking offered by social media in ITE contexts can support PSTs development of linking to their peers (Carpenter, 2015;Carpenter & Morrison, 2018;Duncan-Howell, 2008;Lemon, 2016;Hyndman & Harvey, 2019) while honing reflective practice that illuminates the individual value of skill development associated to the act of being a teacher (Wright, 2010). Use also supports the shift of feeling isolated while in educational settings during the professional experience component of PSTs studies with opportunity for access to conversation with peers, lecturers and the profession and global resources to support their confidence to articulate professional growth (Bull et al, 2008;Carpenter, 2015;Carpenter & Morrison, 2018;Lemon, 2016;Lemon, Molloy & Hocking, 2015).…”
Section: Social Media In Initial Teacher Educationmentioning
confidence: 99%
“…In integrating social media into ITE, it has however, been reported that it is not uncommon for PSTs to not be aware of personal to professional transfer of use (Lemon, 2016;Nielsen et al, 2013;Mendez et al, 2009), with authentic connections required (Hyndman & Harvey, 2019;Lemon, 2019). This provides opportunity to support PSTs capacity to consider how platforms that exist beyond the university learning management systems can support a crucial element in authentic adaption for both professional development, and to supporting teaching of ITE content (Bull et al, 2008;Lemon et al, 2015;Hyndman & Harvey, 2019).…”
Section: Social Media In Initial Teacher Educationmentioning
confidence: 99%
See 3 more Smart Citations